Integration of Education for Sustainable Development in teacher education, Life Sciences classroom practices, during the Covid pandemic - Ndelu, Sethabile (University of the Witwatersrand, Johannesburg, 2024)
Education for Sustainable Development (ESD) has been identified as a key vehicle for achieving the Sustainable Development Goals (SDGs), and teachers have a critical role to play in promoting ESD. This study investigates the integration of ESD in teacher education, specifically in the Life Sciences classroom during the Covid-19 pandemic. The study utilised qualitative research methods, including interviews with two Life Sciences teacher educators and open-ended questionnaires sent to ten prospective teachers. Data was also obtained from the teacher educators’ course outlines and the Life Sciences Curriculum Assessment Policy (CAPS). The findings suggest that ESD integration is largely dependent on the teacher educator’s agency, as the teacher training institution did not provide adequate institutional and pedagogical guidance for integrating ESD into teacher practices. The Covid-19 pandemic led to online learning, which restricted the practical application of ESD competencies in real-life change projects.
A research report Submitted in fulfillment of the requirements for a Master of Education, In the Faculty of Humanities , Wits School of Education, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Sustainable development (SD); Education for Sustainable development (ESD) Life Sciences curriculum; Covid-19 pandemic; SDG-4: Quality education; SDG-17: Partnerships for the goals